Co-Infection of Chicken Infectious Anemia Virus and Fowl Adenovirus Serotype E8b Increases Mortality in Chickens - Lin Liu; Wenming Gao; Jingjing Chang; Jingrui Liu; Zongmei Huang; Wenjie Sun; Yapeng Song; Xinsheng Li (Viruses)
The chicken infectious anemia virus (CIAV) and fowl adenovirus serotype E8b (FAdV E8b) are pathogens that cause aplastic anemia and inclusion body hepatitis (IBH) in chickens, respectively. The co-infection of CIAV and FAdV E8b poses a significant threat to poultry health, potentially worsening clinical symptoms and increasing mortality rates. This study aimed to explore the combined pathogenic effects of FAdV E8b and CIAV co-infection on one-day-old specific pathogen-free (SPF) chickens. The results showed that co-infection led to significantly higher clinical scores and mortality rates compared to FAdV E8b infection alone. Additionally, there were different tissue distribution patterns for FAdV E8b between the single infection and co-infection groups, indicating potential changes in viral tropism. Biochemical analysis revealed elevated markers of liver and/or muscle damage in both the FAdV E8b infection group and the co-infection group, consistent with the viral infection process. These findings suggest that co-infection with FAdV E8b and CIAV can intensify clinical signs and mortality, and may potentially alter viral replication and tissue tropism in chickens. This study establishes a foundation for future investigations into the underlying mechanisms governing the interaction between CIAV and FAdV E8b during co-infection.